SWELLING POTENTIAL OF CLAY SOIL KALIWANGU FORMATION IN CIBOGO DISTRICT, SUBANG REGENCY AREA BASED ON ITS BASIC PHYSICAL PROPERTIES - Prasetio, Rio Akmal Rizky; Sophian, Raden Irvan; Firmansyah, Yusi; Khoirullah, Nur (Faculty of Geological Engineering, Universitas Padjadjaran, 2023)
The research is conducted in Cibogo District, Subang Regency. Focus of the research is taking samples in area inside Kaliwangu Formation by doing field observation and field sampling using disturbed sample method then it will be tested in laboratory for its basic physical properties. Result of its basic physical properties will be analyzed to determine their swelling potential by taking 5 sample of soil from Kaliwangu Formation. Based on sieve analysis every sample of Kaliwangu Formation (Pk) have more than 50% of clay fraction for each sample, and based on Atterberg limit test Kaliwangu Formation (Pk) samples are dominated by Silt High Plasticity (MH) soil with 3 samples of the MH type and only 2 samples of the CH type. According to consistency limit test of Kaliwangu Formation (Pk) soil, the swelling potential can be determined by classify it based on liquid limit (%) and plasticity index (%) using swelling potential classification. Using the soil consistency value, especially the liquid limit value and the plasticity index value, it can be classified as the swelling potential of Kaliwangu Formation (Pk) classified as high - very high potential with a very high dominance.